A Hydrogen Bonds-Crosslinked Hydrogels With Self-Healing and Adhesive Properties for Hemostatic - Yu, Han; Xiao, Qiaohong; Qi, Guilin; Chen, Feixiang; Tu, Biyue; Zhang, Suo; Li, Yinping; Chen, Yun; Yu, Hui; Duan, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogels with adhesive properties have the potential of rapid hemostasis and wound healing in uncontrolled non-pressurized surface bleeding. Herein, a typical hydrogen bond-crosslinked hydrogel with above functions was constructed by directly mixing the solutions of humic acid (HA) and polyvinylpyrrolidone (PVP), in which the HA worked as crosslinking agent to form hydrogen bond with PVP. By altering the concentration of HA, a cluster of stable and uniform hydrogels were prepare within 10 seconds. The dynamic and reversible nature of hydrogen bond made the HA/PVP complex (HPC) hydrogel have injectable ability, good flexibility, and self-healing ability. Moreover, the numerous functional groups existed in the hydrogel enhanced the cohesion strength and interaction on the interface between hydrogel and substrate, which endowed the hydrogels with good adhesion property. Unique chemical composition and cross-linking mechanism made the HPC hydrogel exhibit good biocompatibility. Taking advantage of all these features, the broad application of the HPC hydrogels obtained in this work in hemostatic agent was carried out and showed good therapeutic effect. This work might lead to improvement in the development of multifunctional non-covalent hydrogel to be applied in biomaterials.